PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, DAN MOTIVASI TERHADAP KINERJA PERSONIL RESKRIM POLRESTA BANJARMASIN - Andik Ariyanto; Titien Agustina (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Personil of Reskrim Polresta Banjarmasin improve the work performance for service quality improvemtn. The Performance is influenced by emotional intellegent, intellectual intellegent, and work motivation. To analyzing and to know the influence of those variables to the work performance need the research. Quantitative method is used in the research. The population is all members of the police namely 60 persons. Technique of sampling is census. This research sample 60 person. The data collection technique is questioner. Data is analyzed by linier regression analysis. The results of this research shows that intellegent, intellectual qoution, and work motivation have influence significantly to the performance partially and together. The emotional intellegent, intellectual intellegent, and work motivation are need to improve because these variables have influence significantly to the performance.